Pure androgen-secreting adrenal tumor (PASAT): A rare case report of bilateral PASATs and a systematic review - Liao, Zhangcheng; Gao, Yuting; Zhao, Yang; Wang, Zhan; Wang, Xu; Zhou, Jiaquan; Zhang, Yushi (Frontiers in Endocrinology, 2023)
Background: Adult pure androgen–secreting adrenal tumours (PASATs) are extremely rare, and their characteristics are largely unknown. Methods: A rare case of adult bilateral PASATs is reported, and a systematic literature review of adult PASATs was conducted to summarize the characteristics of PASATs. Results: In total, 48 studies, including 40 case reports and 8 articles, were identified. The average age of 42 PASAT patients was 40.48±15.80 years (range of 18-76). The incidence of adult PASAT peaked at 21-30 years old, while that of malignant PASAT peaked at 41-50 years old. Most PASAT patients were female (40/42, 95.23%), and hirsutism was the most common symptom (37/39, 94.87%). Testosterone (T) was the most commonly elevated androgen (36/42, 85.71%), and 26 of 32 tested patients presented increased dehydroepiandrosterone sulfate (DS) levels. In malignancy cases, disease duration was significantly decreased (1.96 vs. 4.51, P=0.025), and tumour diameter was significantly increased (8.9 vs. 4.9, p=0.011). Moreover, the androgen levels, namely, T/upper normal range limit (UNRL) (11.94 vs. 4.943, P=0.770) and DS/ UNRL (16.5 vs. 5.28, P=0.625), were higher in patients with malignancy. In total, 5 out of 7 patients showed an increase in DS or T in the human chorionic gonadotropin (HCG) stimulation test. Overall, 40 out of 41 patients underwent adrenal surgery, and recurrence, metastasis, or death was reported in 5 out of 11 malignant patients even with adjuvant or rescue mitotane chemotherapy. Conclusion: Adult PASAT, which is predominant in women, is characterized by virilism and menstrual dysfunction, especially hirsutism. Elevated T and DS may contribute to the diagnosis of adult PASAT. Patients with malignant PASAT have a shorter disease duration, higher androgen levels and larger tumour sizes. Surgery is recommended for all local PASATs, and PASAT malignancy should be considered due to the high risk of malignancy, poor prognosis and limited effective approaches.